Relações entre regulação emocional, coping diádico e a qualidade da relação coparental - Almeida, Regiane Fernandes da Silva (Universidade Federal de São Carlos, 2024)
During the transition to parenthood, two-thirds of couples experience hostile conflicts in the coparental relationship, with negative effects on marital relationships, parents' mental health, and the socioemotional development of the child. Emotional regulation skills and dyadic coping may be important in this context, but it is necessary to obtain evidence about the relationships among these skills and the quality of the coparenting relationship. The objective of this study was to investigate the relationships among emotional regulation skills, dyadic coping skills, and the quality of the coparenting relationship. Participants included 48 fathers and 58 mothers, aged 18 to 48, who were caring for their first child aged up to 6 years. Parents were recruited via social etworks and responded to a socio-economic questionnaire, the Emotional Self-Regulation Scale for adults, the Dyadic Coping Inventory, and the Coparental Relationship Scale, via Google Forms. Based on bivariate correlation analyses, statistically significant but weak relationships were observed between: (a) the use of appropriate emotional regulation strategies and constructive forms of coping in the dyadic relationship, as well as the use of inappropriate emotional regulation strategies and difficulties in dealing with stressful situations with the partner; (b) the use of appropriate emotional regulation strategies and higher quality of the coparental relationship in all dimensions, and the use of inappropriate strategies and lower quality results in this relationship; (c) a greater ability to cope with stress in interactions with the coparenting partner and better results in all dimensions of the coparenting relationship. Thus, evidence was found indicating the relevance of emotional self regulation skills and the ability to team up with one’s partner to respond to stressful situations for the quality of the oparenting relationship. The limitations of this study in terms of sample profile involve a problem of suppression of variance, and point to the importance of using more varied recruitment strategies to form more representative samples, in future studies. In conclusion, the results of this study contribute to the literature on socioemotional skills that affect the quality of the coparenting relationship, aiding in the development of evidence-based psychoeducation programs to help parents of young children develop their emotional regulation and dyadic coping skills in this context.
Relationships among emotional regulation, dyadic coping and the quality of the coparenting relationship
Keywords: Coparentalidade; Coping diádico; Habilidades socioemocionais; Coparenting; Dyadic coping; Socioemotional skills; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::RELACOES INTERPESSOAIS